CARES ASSISTANCE IN DEVELOPING INDEPENDENT TREATMENT OF TYPE 2 DIABETES MELLITUS PATIENTS IN MANTUIL VILLAGE, BANJARMASIN SELATAN DISTRICT - Taufika Sari, Rohni (Sean Institute, 2022)
The high incidence of Diabetes Mellitus (DM) impacts all aspects of patient life. The main focus of DM management is changing lifestyles. Lifestyle management is fundamental in DM care, such as self-learning management, care support, physical activity, smoking counseling, and psychosocial care. It is hoped that lifestyle changes can improve glycemic control and reduce complications and death. Health cadres are given empowerment programs as motivators and mentors in comprehensive self-care. The main program in community service is assisting cadres in empowering type 2 DM patients. This activity begins with a pre-test by giving questions in the form of a questionnaire. The implementing team provides the material following the contents of the module. The mentoring program is carried out after the material delivery is complete. Assistance for cadres is carried out by directly inviting type 2 DM patients to Mantuil Village, South Banjarmasin District. Partners were divided into small groups of 5-6 people. After being given material presentation and assistance, there was an increase in the partner's ability to empower type 2 DM patients. This increase occurred significantly, namely 85.7%, in the good category.